Determination of Chemical Composition and Investigation of Biological Activities of Ocimum basilicum L. - Qasem, Ahmed; Assaggaf, Hamza; Mrabti, Hanae Naceiri; Minshawi, Faisal; Rajab, Bodour S; Attar, Ammar A; Alyamani, Reema A; Hamed, Munerah; Mrabti, Hanae Naceiri; El Baaboua, Aicha; El Omari, Nasreddine; Alshahrani, Mohammed Merae; et al. (MDPI, 2023)
This study aimed to determine the chemical composition of the essential oils (EOs) of Ocimum basilicum L., as well as to evaluate the antibacterial, antidiabetic, dermatoprotective, and anti-inflammatory properties, and the EOs and aqueous extracts of O. basilicum. The antibacterial activity was evaluated against bacterial strains, Gram-positive and Gram-negative, using the well diffusion and microdilution methods, whereas the antidiabetic activity was assessed in vitro using two enzymes involved in carbohydrate digestion, α-amylase and α-glucosidase. On the other hand, the dermatoprotective and anti-inflammatory activities were studied by testing tyrosinase and lipoxygenase inhibition activity, respectively. The results showed that the chemical composition of O. basilicum EO (OBEO) is dominated by methyl chavicol (86%) and trans-anethol (8%). OBEO exhibited significant antibacterial effects against Gram-negative and Gram-positive strains, demonstrated by considerable diameters of the inhibition zones and lower MIC and MBC values. In addition, OBEO exhibited significant inhibition of α-amylase (IC50 = 50.51 ± 0.32 μg/mL) and α-glucosidase (IC50 = 39.84 ± 1.2 μg/mL). Concerning the anti-inflammatory activity, OBEO significantly inhibited lipoxygenase activity (IC50 = 18.28 ± 0.03 μg/mL) compared to the aqueous extract (IC50 = 24.8 ± 0.01 μg/mL). Moreover, tyrosinase was considerably inhibited by OBEO (IC50 = 68.58 ± 0.03 μg/mL) compared to the aqueous extract (IC50 = 118.37 ± 0.05 μg/mL). The toxicological investigations revealed the safety of O. basilicum in acute and chronic toxicity. The finding of in silico analysis showed that methyl chavicol and trans-anethole (main compounds of OBEO) validate the pharmacokinetics of these compounds and decipher some antibacterial targets.